Реалізація ресурсного підходу в системі педагогічної підготовки майбутніх учителів: світовий досвід - Микитюк, Сергій Олександрович (НТУ "ХПІ", 2013)
У статті конкретизуються окремі аспекти реалізації завдань щодо вдосконалення змісту вищої педагогічної освіти через розроблення та впровадження відповідного науково-методичного супроводу навчально-виховного процесу на базі ресурсного підходу. На підставі аналізу документа "Загальні європейські принципи і підходи до компетентностей та кваліфікацій учителів", які покладені в основу створення єдиної структури європейської якості педагогічної освіти, визначено ключові ознаки педагогічної професії у контексті реалізації ресурсного підходу.

The author elaborated on certain aspects of the implementation of tasks to improve the content of higher pedagogical education through the development and implementation of appropriate scientific and methodological support of the educational process on the basis of the resource approach. Based on the "Common European principles and approaches to the competences and qualifications of teachers", the underlying structure of the creation of a single European quality of teacher education, identified the key characteristics of the teaching profession in the context of the resource approach
Implementation of the resource-based approach in the system of future teacher training: international experience
Keywords: інтеграція; педагогічна освіта; студент; resource-based approach; integration; teacher education; teacher profession; student